(3efJNH ef MdjI GdChdjGA dCHj fYje GdCUagGfj GdeJhajSfI (B430 (3g`s - (3eLghds; (3CHh fYje,J (B430 (3g` s
(3ChdgG (B:s
(3Gddge CjOfG EPG YHOfGc gPG hdeG JUaMJ Yf efGbH GdSGOI GdCHQGQ aeG hLOJ cJGHkG CMSf JCdjakG aj MdjI GdChdjGA ef GdoeUfa GdPi QJHg s
(3hbO CgOGg Edi NRGfI CHj GdbGSe gGQhf Hf Ydjs
(3JHUQI GdYfhGf (B:s
(3GNJjGQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B157 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B1 - (3U (B282s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B4 - (3U (B433 s
Keywords: (3GdJGQjNs